UTILIZATION OF BIOGAS USING PORTABLE BIOGAS ANAEROBIC DIGESTER IN REMOTE AREAS OF SHIKARPUR AND SUKKUR DISTRICTS: A CASE STUDY - A. N. Sanjrani; S. A. Shah; M. N. Sanjrani; S. A. Sheikh; M. Malhi (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2017)
Wood and natural gas are used as fuel for heating and cooking in country side. With the rapid growth in population, the demand of these resources has significantly increased, creating a bewildering shortfall of energy. This shortfall of the energy could be overcome by utilizing available natural energy sources.  Biogas can be generated and utilized as an alternative source of energy; particularly for cooking, heating and power generation on small scale. Therefore, a case study on existing biomass sources such as dung was carried out in some rural areas of Shikarpur and Sukkur districts. In these areas the animal waste is generated in huge quantity that can be processed using any portable digester like a portable anaerobic digester used in this study. It is evident from this case study that the portable digester has a potential to generate biogas for domestic consumption. The selected digester can be used to produce methane rich gas, as an alternative to wood and natural gas supply in these areas.